A Critical Discourse Analysis of Canada's Throne Speeches Between 1935 and 2015 - Johnstone, Justin (My University, 2017)
The purpose of this thesis was to uncover the tools of manipulation used within political discourses by governments in their attempt to maintain power in society. It specifically asked, How do Canadian federal governments manipulate security, risk, and threat discourses alongside their presentation and understanding of Canadian identity in throne speeches to justify the direction they intend to take the country in with their mandate? This thesis used Critical Discourse Analysis methods to analyze fourteen federal majority government speeches from the throne during the rise and fall of social welfare in Canada. Findings highlight that governments have relatively consistently used the combination of security, risk, and threat discourses between 1935 and 2015. Canadian identity has also been shown to be malleable to government priorities, being connected to notions of collectivism during the rise of social welfare and individualization and productivity during the implementation of neoliberal principles. The introduction of the promise of job creation within the speeches was found to correlate with the introduction of neoliberal principles in Canada. These findings highlight the importance of critical understanding of dominant discourses in society in order to overcome the power they can impose over non-dominant groups.
Keywords: discourse analysis; speeches from the throne; government discourse; social welfare and neoliberalism